Anti-Obesity and Anti-Hypertensive Action of Calanus Oil - Salma, Wahida (UiT The Arctic University of Norway, 2015)
The papers of this thesis are not available in Munin: I. Höper, Anje Christina; Salma, Wahida; Khalid, Ahmed Murtaz; Hafstad, Anne Dragøy; Sollie, Selene Julie; Raa, Jan; Larsen, Terje; Aasum, Ellen. Oil from the marine zooplankton Calanus finmarchicus improves the cardiometabolic phenotype of diet-induced obese mice. British Journal of Nutrition 2013; Volum 110. s. 1145 2186 - 2193. Available at http://dx.doi.org/10.1017/S0007114513001839 II. Höper, Anje Christina; Salma, Wahida; Sollie, Selene Julie; Hafstad, Anne Dragøy; Lund, Jim; Khalid, Ahmed Murtaz; Raa, Jan; Aasum, Ellen; Larsen, Terje. Wax esters from the marine copepod calanus finmarchicus reduce diet-induced obesity and obesity-related metabolic disorders in mice. Journal of Nutrition 2014; Volum 144 (2), s.164 – 169. Available at http://dx.doi.org/10.3945/jn.113.182501 III. Salma W, Franekova V, Lund T, Höper AC, Ludvigsen S, Lund J, Aasum E, Ytrehus K, Belke DD, Larsen TS. Dietary Calanus oil antagonizes angiotensin II-induced hypertension and tissue wasting in obese mice. Manuscript submitted in American journal of Physiology. (Manuscript). In this doctoral project we have examined the biological effects of Calanus oil in a mouse model of obesity. Calanus oil is extracted from the marine copepod Calanus finmarchicus and is one of the richest sources of poly-unsaturated fatty acids in nature. C57BL/6J mice were given a high-fat diet (HFD) over a 27 wk period in order to induce obesity, which was reflected in deposition of considerable amounts of fat in the abdominal cavity and liver. In mice receiving HFD supplemented with a small amount of Calanus oil (1.5%) fat accumulation was significantly less, despite no difference in food intake between the groups. Obesity was also associated with increased expression of genes (mRNA level) coding for pro-inflammatory molecules, as well as macrophage infiltration in adipose tissue, indicative of a local (low-grade) inflammation. Moreover, insulin sensitivity was impaired as documented by reduction in glucose ...